AKTIFITAS KOMUNIKASI MASYARAKAT MELALUI SITUS JEJARING SOSIAL - Yuli Hartono (BPSDMP Kominfo Jakarta, 2011)
With the phenomenal background, activity of a members in public communication through the use of internet in social networking sites. This study focuses in the problem of how communication community activity through social networking sites. With survey refers to activity concept by Levy Katz, and uses concept by Gurevitch and Hass, the research results shows that: variety of custom activities communication in community member when online, through social networking sites, covering 16 different activities. The quantity of activity cover most of the seven types of activities, includes: